2000
DOI: 10.1002/1099-0488(20001015)38:20<2611::aid-polb10>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in the crystalline polymorphic forms I and II and form III of isotactic poly-1-butene

Abstract: Following an earlier study of the 1H relaxation and NMR line shapes, we have carried out selective one‐dimensional and two‐dimensional 13C solid‐state NMR studies that yield to detailed interpretation of the dynamics in form I, II, and III polymorphs of isotactic poly‐1‐butene. A specific defect diffusion along the side group is proposed to account for the temperature dependence of the 13C spectra in form I. The backbone of the helix in forms II and III is shown to undergo large angle motions above the glass‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Studies of cold-drawn high-density polyethylene showed that the "intermediate" component is a primarily all-trans configuration that has higher disorder than the crystalline component (100). Similar studies of the dynamics of isotactic poly(1-butene) have been reported (101). The dynamics of nylon-6 fibers spun at several speeds were examined with NMR, and the NMR properties were shown to change with the spinning rate (102).…”
Section: Synthetic Polymerssupporting
confidence: 61%
“…Studies of cold-drawn high-density polyethylene showed that the "intermediate" component is a primarily all-trans configuration that has higher disorder than the crystalline component (100). Similar studies of the dynamics of isotactic poly(1-butene) have been reported (101). The dynamics of nylon-6 fibers spun at several speeds were examined with NMR, and the NMR properties were shown to change with the spinning rate (102).…”
Section: Synthetic Polymerssupporting
confidence: 61%
“…The observed doublet signals are attributed to the existence of noncongruent two sites, sites A and B, for the constitutional repeating units in form III as illustrated in Figure 2. 14,18 The merge of the split signals above 272 K results from the rapid dynamical exchange between sites A and B within the polymer chains. This exchange is brought about by the 90°helical jump motion of the polymer chains around their helical axes in the crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we use the minimum value (Tg ) 248 K) for i-PB in the literature. [18][19][20] The mixed sample of forms III and I′, heat-treated form III, was prepared by heating the form III-rich sample in an oil bath at 368 K for 1 h. The amorphous sample was obtained by quenching the virgin sample into a liquid nitrogen bath after keeping it in an oil bath at 413 K (above T m of form I) for 5 min. Special attention was paid for the amorphous sample, because the amorphous chains immediately crystallize into form II even at room temperature due to its low Tg.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations